Apical sealing ability of chitosan nanoparticles in epoxy-resin-based endodontic sealer - Raras Ajeng Enggardipta; Raphael Tri Endra Untara; Pribadi Santosa; Aqilla Tiara Kartikaningtyas; Andina Widyastuti; Diatri Nari Ratih (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
A good sealing ability of apical part of root canal system is needed to prevent microleakage thus resulting long-lasting successful treatment. Chitosan nanoparticles as nanofillers could be added to epoxy resin sealer to increase adaptation to dentinal wall. The purpose of this study was to evaluate the apical sealing ability of chitosan nanoparticles addition to epoxy-resin-based sealer. Thirty mandibular premolars were used in this study. The root canals were prepared using rotary files up to #30/0.09. The canal was irrigated with 2.5% NaOCl and 17% EDTA, then was rinsed with sterile water. All teeth were randomly divided into 3 groups (n=10). Group I was obturated with gutta-percha, Group II was obturated with gutta-percha and epoxy resin sealer, group III was obturated with gutta-percha and epoxy resin sealer that was added with chitosan nanoparticles. All specimens were stored in an incubator for 7 days at 37 °C. After that, specimens were tested with centrifuging dye penetration method with methylene blue 2% solution. The specimens were longitudinally sectioned, observed under stereomicroscope (8x magnification) and measured in millimeters (mm). The data were analyzed using one-way Anova. The results of one-way Anova showed that dye penetration in apical part of the root canal in all groups was statistically significant difference. The addition of chitosan nanoparticles to epoxy resin sealer increases the apical sealing ability of root canal obturation material.